'Hombres de otra raza y hasta de otra edad más lejana parecían': Masculinity and Imperial Nostalgia in Eduardo López Bago's El separatista (1895). Issue 9 (20th October 2020) - Copeland, Eva María
Abstract: This essay argues that Eduardo López Bago's 1895 novel El separatista underscores that Cuba should remain a Spanish colony by constructing the Cuban male separatists as deviant to reinforce Spain's imperial hold on Cuba as they reflect peninsular fears about racial degeneration and imperial loss. The text reinforces imperial hierarchies by excluding that which is problematic: white creoles who backed Cuban independence and the black Cubans who fought alongside them. The novel forecloses any possibility that Cuban independence is viable politically, as the text enacts a 'hysterical' reaction to the loss of empire and Spanish men's perceived emasculation.